Management of Private Property and its Topicalities while Lithuania is Integrating into the EU - Bikas, Egidijus (Ekonomika, 2003)
The present article shows that wealth management as a part of life cycle planing, has become a complex task. Wealth management continues to be an attractive business in Lithuania in the future but demands will increase dramatically as client’s are better informed. I introduced some basic concepts conserning wealth managements, financial planing, life cycle concept and modern portfolio management. The emphasis was put on the dimension of financial planing, on wealth management process. The discussion of life cycle model and theory in literature showed that human needs and thus their demands for financial services may change from one life phase to another. Therefore a supplier of financial services can increase decisively added value in offering life cycle adjusted products. Of course there arc needs that can be met with classical, standardised products. When it comes to life events such as inheritance, retirement or tax planning, the complexity rises dramatically.